Quantum computations and density functional theory on corrosion inhibition efficiency of BIA, HBT, MBI and PIZ compounds - D. M. Mamand; H. M. Qadr (Хімія, фізика та технологія поверхні, 2023)
This study determined the corrosion inhibition levels of benzimidazole (BIA), 1-hydroxybenzotriazole (HBT), methylbenzimidazole (MBI) and 4-phenylimidazole (PIZ). By using simulation, it was possible to have a complete relationship with the experimental work because the results were completely consistent. Density functional theory (DFT) and Monte Carlo simulations were used to calculate several quantum chemical parameters. The molecules are simulated using quantum chemical calculations with Gaussian09 software.  Fundamental factors determining the corrosion order of molecules are the highest-energy occupied and lowest-energy unoccupied molecular orbitals (HOMO and LUMO), frontier molecular orbital energy, back donating energy, electrophilicity, nucleophilicity, energy gap ?E, absolute electronegativity (?), softness, the number of electrons (?N) transferred from inhibitors to iron, the dipole moment (?), the global hardness (?) and the total energy.